Servant Leadership, Manajemen Mutu Pendidikan dan Budaya Organisasi Terhadap Kinerja Dosen - Aditya Bachtiar Firmansyah; Sonny Hersona (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
The research was conducted at the University of Singaperbangsa Karawang using quantitative methods, and the number of samples based on saturated sampling was 83 people. The data was collected using an instrument in the form of a statement sheet with a tested Likert scale model. Using linear regression analysis techniques to conduct research, simple correlation, partial or simultaneous. The results of the study concluded that servant leadership had a significant positive effect on the performance of the lecturers at the University of Singaperbangsa Karawang. In this university H1 was accepted or tcount ttable (7,280 1,664); Management of the quality of education of Singaperbangsa Karawang University. Lecturer performance has a significant positive effect, where H2 is accepted or tcount ttable (9.086 1.664); Organizational culture has a significant positive effect on the performance of the lecturers of Singaperbangsa Karawang University, H3 is accepted or tcount ttable (9,469 1,664), and multiplied by servant leadershipand quality management of education has a significant effect on lecturers at Singaperbangsa Karawang. University achievement, accept H4 or F count F table or 56,611 2,720.